Mini-bandstructure tailoring in pi-conjugated periodic block copolymers using the envelope crystalline-orbital method (2010)
A strategy for the systematic design of polymeric superlattices with tailor-made mini-bandgaps and carrier mini-effective masses is described and computationally implemented by means of an envelope crystalline-orbital method, which is a straightforward adaptation for molecules of the envelope-function approximation widely used in solid-state physics. Such strategy relies on the construction of pi-conjugated periodic block copolymers from well-characterized parent polymers, in such a way that the above-mentioned electronic parameters can be predicted from the lengths of the blocks. Illustrative calculations for prototypical (PPP_x-PDA_y)_n superlattices demonstrate the plausibility of the strategy and the advantages of the computational implementation used.